Early-life exposure to mycotoxins: assessing the risk under the earlyMYCO project - Assunção, R. (2021)
Exposure to hazardous chemicals during the first 1000 days of life has been associated to a number of health disorders, e.g. non-communicable diseases. A proper risk assessment built on accurate data assumes particular importance to evaluate the potential impact that early-life exposure could represent in adulthood. Mycotoxins, secondary fungal metabolites, could have harmful effects in humans and animals. Recent studies reported that Portuguese young children are exposed to multiple mycotoxins through food consumption which could constitute a health concern [1]. However, earlier exposure to these compounds remains unexplored. earlyMYCO – Early-life exposure to MYCOtoxins and its impact on health, a national funded project (PTDC/MED-TOX/28762/2017), intends to contribute to clarify this issue evaluating the health effects of early-life exposure of Portuguese mother-and-child pairs to mycotoxins and assessing the associated risk. The associated health risk will be characterized and the health impact assessed combining data from mother-and-child pairs, their exposure to mycotoxins and newly obtained toxicological data. The Estimated Daily Intake (EDI) will be compared with reference dose values. Preliminary results of exposure to mycotoxins through food consumption (cereal-based foods) in young children (≤ 3 years old) revealed a potential adverse health effect for percentiles of intake of aflatoxins above or equal to P50 (corresponding to 0.041 ng/kg body weight/day or higher). Additionally, results also suggest that high levels of exposure to mycotoxins in the early life are more related with processed foods than with breastmilk. Obtained results will contribute to reach an accurate risk assessment framework and to establish and prioritize preventive measures to reduce exposure to chemicals and risk, especially for vulnerable population groups as pregnant women and infants. [1] R. Assunção, et. al., Food and Chemical Toxicology 118, 399–408 (2018).